Inequalities in access to industry‐funded interventional phase I–IV drug trials in epilepsy - Robert Hoepner; Alejandro Xavier León Betancourt; Stefanie Marti; Andrea Seiler (Epilepsia Open)
Abstract Objective Clinical trials on drug safety and efficacy are understood to be valid for all humans, but are not equally distributed worldwide. We aimed to analyze the global distribution of clinical drug trials (phase I–IV) in epilepsy and its correlation with key demographical and epidemiological factors. Methods We combined data on industry‐funded interventional drug trials in epilepsy from clinicaltrials.gov with epidemiological, geographical, socioeconomic, and human development data. This allowed us to analyze the distribution of trials and trial sites in relation to population, epilepsy incidence, and prevalence. Results Among 459 trials conducted in 69 countries, a vast majority of sites were situated in high‐income regions and countries with very high Human Development Index (HDI). There was a striking underrepresentation of low‐income countries and those with low HDI. Specifically, we found a 40‐ to 145‐fold underrepresentation of trial sites in the WHO regions of Africa and the Eastern Mediterranean when comparing the actual number of sites to the expected number, assuming an even distribution by population, incidence, or prevalence. Significance Our findings highlight inequalities in the distribution of epilepsy trial sites based on population size and disease burden. They underscore the need for more equitable trial placement strategies that consider both disease epidemiology and demographic diversity to ensure adequate representation of all affected populations. Plain Language Summary This study looked at where clinical trials for epilepsy medications are being done around the world. We found that most trials take place in high‐income countries, while many areas with a high number of people living with epilepsy—especially in Africa and the Eastern Mediterranean—are left out. This shows a big gap between where the disease is most common and where research happens. Highlighting this mismatch can help guide future efforts to make clinical research more inclusive and globally relevant.